2019
DOI: 10.1103/physreve.99.052902
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity in sheared granular matter

Abstract: We report on experiments investigating the dynamics of a slider that is pulled by a spring across a granular medium consisting of a vertical layer of photoelastic disks. The motion proceeds through a sequence of discrete events, analogous to seismic shocks, in which elastic energy stored in the spring is rapidly released. We measure the statistics of several properties of the individual events: the energy loss in the spring, the duration of the movement, and the temporal profile of the slider motion. We also s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Among the reported experimental studies designed to characterize the avalanche statistics in deformed granular solids (Abed Zadeh et al, 2019; Barés et al, 2017; Denisov et al, 2016; Kumar et al, 2020; Lherminier et al, 2019; Murphy et al, 2019), the avalanche size exponent was found ranging from 1.2 to 1.7, showing a considerable scatter. The cutoff value of avalanche size also shows a clear stress dependency (Denisov et al, 2016; Friedman et al, 2012; Gao et al, 2018; Rivière et al, 2018) and particle shape dependency (Murphy et al, 2019) and is dependent on the particle friction and packing fraction (Barés et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported experimental studies designed to characterize the avalanche statistics in deformed granular solids (Abed Zadeh et al, 2019; Barés et al, 2017; Denisov et al, 2016; Kumar et al, 2020; Lherminier et al, 2019; Murphy et al, 2019), the avalanche size exponent was found ranging from 1.2 to 1.7, showing a considerable scatter. The cutoff value of avalanche size also shows a clear stress dependency (Denisov et al, 2016; Friedman et al, 2012; Gao et al, 2018; Rivière et al, 2018) and particle shape dependency (Murphy et al, 2019) and is dependent on the particle friction and packing fraction (Barés et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it may be directly applied in other fields such as nanofluidics or nanomagnetism where crackling and random large-scale events are to be limited. More generally, we believe these results can be somehow extended to other crackling systems such as sheared granular matter [11,27,30,31], damage [6,7], neural activity [32,33], human conflicts [34,35], or seismicity [36,37] to name a few.…”
Section: Concluding Discussionmentioning
confidence: 64%
“…Then, the temporal avalanche shape was examined. This observable provides an important characterization of crackling signals [4,26,27]. This shape is obtained by (i) identifying all avalanches with durations D i falling into a prescribed in- terval and then (ii) by averaging the shape v i (t )/v i max vs t/D i over all the collected avalanches.…”
Section: Role Of the Triggering Methodsmentioning
confidence: 99%
“…Many mechanical systems other than crustal faults exhibit crackling noise when plastically deformed (10,11,15,27,(44)(45)(46). In particular, the statistical properties of deformation or mechanical stress fluctuations follow power laws which reveal the absence of any particular scale in the system at least in an extended inertial (scale) range.…”
Section: Discussionmentioning
confidence: 99%
“…Power-law distributions of slip sizes or relaxed energies have been evidenced experimentally in various systems, such as the stationary propagation of a fracture front in a heterogeneous material (10), compression of heterogeneous materials (11,12), or systems involving frictional sliding on or within a granular media (13,14). The common basic ingredients underlying the dynamics of those different systems are the existence of material disorder and the decomposition of the dynamics in elementary events localized both in space and time, coupled together by elasticity.…”
mentioning
confidence: 99%